An Overview on Immunogenic Cell Death in Cancer Biology and Therapy - Mosar Corrêa Rodrigues; José Athayde Vasconcelos Morais; Rayane Ganassin; Giulia Rosa Tavares Oliveira; Fabiana Chagas Costa; Amanda Alencar Cabral Morais; Ariane Pandolfo Silveira; Victor Carlos Mello Silva; João Paulo Figueiró Longo; Luis Alexandre Muehlmann (MDPI AG, 2022)
Immunogenic cell death (ICD) is a modality of regulated cell death that is sufficient to promote an adaptive immune response against antigens of the dying cell in an immunocompetent host. An important characteristic of ICD is the release and exposure of damage-associated molecular patterns, which are potent endogenous immune adjuvants. As the induction of ICD can be achieved with conventional cytotoxic agents, it represents a potential approach for the immunotherapy of cancer. Here, different aspects of ICD in cancer biology and treatment are reviewed.